2021
DOI: 10.1038/s41598-021-95059-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CSF1R, a receptor involved in microglia viability, alters behavioral and molecular changes induced by cocaine

Abstract: Different data suggest that microglia may participate in the drug addiction process as these cells respond to neurochemical changes induced by the administration of these substances. In order to study the role of microglia in drug abuse, Swiss mice aged 8–9 weeks were treated with the CSF1R inhibitor PLX3397 (40 mg/kg, p.o.) and submitted to behavioral sensitization or conditioned place preference (CPP) induced by cocaine (15 mg/kg, i.p.). Thereafter, brains were used to evaluate the effects of CSF1R inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 110 publications
(147 reference statements)
1
12
1
Order By: Relevance
“…However, the percentage of depletion we observed is lower than what was previously reported in other studies using a lower dose of PLX3397 through oral gavage (40 mg/kg) (M. Yang et al, 2018). Another team also found a lower depletion rate (around 50%) in the nucleus accumbens of Swiss male mice (da Silva et al, 2021). These discrepancies between studies could be due to depletion efficacy variability between species, sexes and brain regions.…”
Section: Discussioncontrasting
confidence: 93%
“…However, the percentage of depletion we observed is lower than what was previously reported in other studies using a lower dose of PLX3397 through oral gavage (40 mg/kg) (M. Yang et al, 2018). Another team also found a lower depletion rate (around 50%) in the nucleus accumbens of Swiss male mice (da Silva et al, 2021). These discrepancies between studies could be due to depletion efficacy variability between species, sexes and brain regions.…”
Section: Discussioncontrasting
confidence: 93%
“…The low dose of PLX3397 had no effect on microglial density or soma area but significantly increased the total length and maximum length of microglial processes in the male mouse hippocampus. The high dose of PLX3397 significantly increased the intersections of microglial processes in males, which is consistent with a previous report (da Silva et al, 2021). It seems that the low and high doses of PLX3397 do not significantly increase microglial soma size.…”
Section: Discussionsupporting
confidence: 93%
“…It seems that the low and high doses of PLX3397 do not significantly increase microglial soma size. A recent study reported that PLX3397 can increase the cell body to total cell size ratio of Iba1‐ir cells (da Silva et al, 2021). The results showed that there was no significant difference in microglial density in the hippocampus of mice treated with PLX3397 for between seven and 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that CBD had a general effect of reducing microglial activation, but cocaine sensitization avoided this effect. It is known that treatment with cocaine can increase Iba‐1 staining (Burkovetskaya et al., 2020; Cotto et al., 2018; da Silva et al., 2021). Both cocaine use and abstinence affect the expression of regulatory genes necessary for the proper functioning of glial cells, demonstrating the importance of these cells in the adaptive changes that the brain undergoes due to drug exposure (Hayakawa et al., 2008).…”
Section: Discussionmentioning
confidence: 99%